Auditory steady-state response in the first six months of life - Oliveira, Luciana Cristina (2014)
Objective: To characterize the thresholds of the auditory steady-state response that relates to term newborns and infants. Design: The study was cross-sectional using auditory steadystate response assessment, and the real-ear-to-dial difference was measured in the external auditory canal. Study Sample: The study group included 60 newborns and infants between the age of 0 and 6 months. Results: A statistically significant difference was found in the carrier frequency variable for auditory steady-state response thresholds but not in comparison to ages. Furthermore, there is an association between auditory steady-state response thresholds and the real-ear-to-dial difference. Conclusion: The same threshold can be used as a normality reference for this age range, with distinct values for the different carrier frequencies. The influence of external auditory canal amplification should be taken into account.